Trajectory tracking control of a flexible air-breathing hypersonic vehicle using Lyapunov-based model predictive control - Haiyan Gao; Zhichao Chen; Weiqiang Tang (Systems Science & Control Engineering)
Considering the constraints of inputs and angle of attack (AOA), the trajectory tracking control of a flexible air-breathing hypersonic vehicle (FAHV) is investigated. To solve the problem, the Lyapunov-based model predictive control (LMPC) is presented. Firstly, the virtual controller is designed by nonlinear backstepping control (BSC), and it is integrated into the Lyapunov contraction constraint in LMPC to ensure the stability of the closed-loop system. Secondly, LMPC law is obtained by optimizing the weighted summation performance index of the tracking error and the control. Within the LMPC framework, the input constraints and AOA constraints can be handled simply, and by designing the appropriate parameters of the virtual controller, closed-loop stability is achieved. The effectiveness and superiority of the proposed method are verified by comparing it with the BSC and traditional model predictive control.